Pemanfaatan Aloevera Sebagai Moist Dressing Dalam Penanganan Pertama Luka Bakar Berbasis Sekolah - Nian Afrian Nuari; Efa Nur Aini; Ar. Rachmadyna Shirfie (STIKes Ibnu Sina Ajibarang, 2023)
Education about the use of family medicinal plants (TOGA) currently really needs to be disseminated early to school students to increase knowledge as medicine and food. The aim of this community service is to increase students' understanding of using TOGA plants earlier, especially aloe vera which is used for first aid in burn wound management. This activity was carried out by presenting material and demonstrations with 30 high school students as respondents. The results of activities before the educational intervention were carried out were found to be an average (53.00) and after the educational intervention was given an average (80.00). So, from the results of the average points before and after being given burn wound management education based on aloe vera moist dressing, it was found that there was an increase in Senior High School students' knowledge and insight regarding burn wound management. Aloevera contains sterols including campesterol, β-sitosterol, and cholesterol which can reduce inflammation, help in reducing pain and act as a natural analgesic. Aloevera Moist Dressing for burn wound management can be used as an alternative for treating burns at home independently, because it is quite easy to use and the aloevera ingredient is easy to find.